Penambangan Pasir Komersil di Desa Koto Kandis Tanjung Jabung Timur ditinjau dari Hukum Islam - Tri Kurnia Ningsih; Bahrul Ma'ani; Masnidar Masnidar (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2016)
This study uses the Islamic legal approach with qualitative research methods with techniques for collecting data through observation, interviews, and documentation. The research aims to reveal the commercialization of sand mining in Koto Kandis Village, Dendang District, East Tanjung Jabung Regency, and see how Islamic law views the sand mining activities carried out by the community in Koto Kandis. Based on the research carried out, the results are as follows: First, the process of commercializing sand mining is carried out by the Kandis City farmers using water and land lines. Second, this sand mining has positive impacts such as being able to increase economic income and help meet children's educational needs and deepen river water for smoother waterway trips. The negative impact of sand mining is road damage, air pollution due to dust, increased noise due to sand transport trucks, and a decrease in water quality due to sand mining. Third, in the view of Islam, natural resources in its essence belong to Allah's absolute mandated management, utilization and preservation to humans. In the management, exploration and exploitation of natural resources must pay attention to the preservation of nature and the environment and the sustainability of development. In the process of commercializing sand mining that occurs in Koto Kandis Village can be viewed from various aspects included in Islamic law including: Judging from the Word of Allah SWT in the Qur'an, Judging from the Word of the Prophet Muhammad, Judging from the Fatwa of the Indonesian Ulema Council (MUI) , Judging From the Istinbath Method of Islamic Law, Viewed From the Muhammadiyah Tarjih, Judging From the Principles of Fiqh.